Management of Organic Waste into Compost Fertilizer Planting Media in Talang Buluh District, Banyuasin Regency - Nofrima, Sanny; Sari, Katherina (Universitas Muhammadiyah Makassar, 2024)
This journal discusses the management of organic waste which is converted into compost planting media in a short time, only in one second at the Buddhi Gardens of the New Culture Center, Talang Buluh, Banyuasin Regency. This study aims to explain the process of processing household waste into compost and used as a planting medium that is useful for life, as well as reducing waste generation, especially in Palembang City. The research method applied is a qualitative method with a case study and descriptive approach. The research instruments used included interviews, direct observation, documentation, and researchers as the main instruments. The data source used is the results of interviews with the founder, admin, and workers of Kebun Buddhi. The results of the study show that the waste problem is still an unresolved issue in Indonesia and the world, especially in the city of Palembang which produces around 1,180 tons of waste per day. Kebun Buddhi is here as an innovation to overcome this problem by managing organic waste to become a compost planting medium in a short time which is useful to improve the quality of plants and reduce the negative impact of organic waste on the environment and health. Apart from that, Kebun Buddhi also plays a role in educating the public about managing organic waste to become compost planting media, as part of efforts to support sustainable and environmentally friendly waste management programs.